STUDI PENERAPAN AKUSTIK PADA GERBONG KERETA API SRI LELAWANGSA - Riri Angriani Nasution; Zubair Aman Daulay; Abdul Halim Daulay (Komunikasi Fisika Indonesia, 2023)
This study aims to determine the noise level in the Sri Lelawangsa train carriage without the addition of sound-absorbing materials and to determine the thickness of the sound-absorbing material needed to meet the acoustic comfort standard if it is simulated in a sample testing room. Noise level measurements were carried out on the Sri Lelawangsa train carriages in conditions without the addition of sound-absorbing materials. This noise level measurement was carried out in three carriages of the Sri Lelawangsa train, namely the train carriage, engine carriage, and passenger carriage, the source of noise comes from outside and inside the Sri Lelawangsa train. The study of the application of acoustics was carried out in a sample testing room made of cardboard boxes with a length of 34cm, width 25, cm and height 32 cm, and the source of noise in the sample testing room was the speaker. The absorbent material used to meet the acoustic comfort standard is pyramidal foam which is placed on the nearest side of the sound source. The measuring instrument used to measure noise on the Sri Lelawangsa train is a sound level meter and the Surfer Golden V16 software is used to describe the distribution of sound in the Sri Lelawangsa train carriage. The noise level on the Sri Lelawangsa train still exceeds the quality standard set by the Regulation of the Minister of Transportation of the Republic of Indonesia No. 75 of 2015 which is 80 dB. The highest noise level in the passenger car is at point (1) 82.81 dB. The machinist carriage is 84.70 dB, and the engine carriage is at point (2) 88.92 dB. After measuring the reverberation time on the Sri Lelawangsa train carriage, it is known that the surface area of the sound absorbing material needed to meet the reverberation time standard on the Sri Lelawangsa train carriage is 34,83 m3 with an absorption coefficient (α) of 0.58 according to with the provisions of SNI 03-6306-2000.